Improving the properties of binder jetted ceramics via nanoparticle dispersion infiltration. Issue 22 (15th November 2022) - Zhao, Huoping; Wang, Ajin; Li, Ganghui; Hu, Qiang; Ye, Chunsheng; Shen, Mingxue; Xiao, Yelong; Liu, Shaopeng; Ji, Dehui
Abstract: To improve the dimensional accuracy, surface quality, and mechanical properties of binder jet additive manufactured ceramic parts, in this work, nanozirconia dispersion and binder were used to prepare a jet solution to investigate the effect of nanozirconia content of the jet solution on the properties of zirconia ceramic green and sintered bodies. When the nanozirconia content of the jet solution increased from 0 to 20 wt%, the forming precision of the zirconia ceramic green bodies improved, the surface roughness decreased, and the density increased. After sintering at 1400 °C for 2 h, linear shrinkage along the height, width, and length of the zirconia ceramics decreased by 6.27%, 10.20%, and 5.45%, respectively, while the surface roughness decreased by 42.87%, and the bending strength increased by 145.60%. With increasing nanozirconia content of the jet solution, the spreading and infiltration distance of the jetted solution in the powder layer decreased, the thickness of the deposition layer of nanozirconia on the surface of the zirconia particles in the powder layer increased, and the pore size of the powder layer decreased significantly. This increased the density of the green bodies; thus, improving the sintering properties of the zirconia ceramics.